THE RELATIONSHIP BETWEEN FAMILY SUPPORT WITH DENTAL HYGIENE IN STUDENTS OF SDN 04 CUBADAK AIR - AULIA, FAJRI FEBRINI; YUSRA, REZKI YETI; ANDRIANI, LINDA (As-Shiha : JOURNAL OF MEDICAL RESEARCH, 2025)
Good dental hygiene is an important aspect in maintaining oral health and preventing various dental diseases, such as caries and periodontal disease. In childhood, knowledge about how to maintain dental hygiene is often still limited, so family support plays a very important role in forming good dental care habits. This study aims to determine the relationship between family support with dental hygiene in students of SDN 04 Cubadak Air. The research method used is an analytical survey with a cross-sectional approach. The population of the study were students of SDN 04 Cubadak Air. The sample of this study consisted of 61 students of SD 04 Cubadak Air who were selected randomly (random sampling). Data were collected through questionnaires to measure the level of knowledge and family support and dental hygiene examinations. The results showed that a relationship between family support (p-value = 0.004 < α = 0.05) and students' dental hygiene. In conclusion, family support is related to dental hygiene in students of SDN 04 Cubadak Air. The researcher's suggestion is that teachers can remind students' families to be more active in providing education about dental care for children.